Functional foods, beverages, and ingredients in athletics - Spano, M. (Strength and Conditioning Journal, 2010)
FUNCTIONAL FOODS AND BEVERAGES ARE GROWING IN SALES AND TOTAL NUMBER OF PRODUCTS. MANY OF THESE PRODUCTS ARE MARKETED TOWARD HEALTH-CONSCIOUS AND/OR ACTIVE INDIVIDUALS, MAKING ATHLETES PRIME CONSUMERS. THIS REVIEW EXAMINES THE RESEARCH BEHIND FUNCTIONAL FOODS AND BEVERAGES AND THEIR POTENTIAL APPLICATION IN VARIOUS SPORTING ENDEAVORS.